Fundamental Provisions of the Concept of Balanced Interaction of Society and Nature as Basis of Sustainable Development of the World - A. V. Demidov; А. I. Pashovkin (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The concept of balanced interaction of society and nature as the foundation of sustainable development of the world was built on the basis of researching the current trends of evolution of ecological tool management, studying theoretical principles of enterprise management as an ecological-economic system, practical experience of carrying out environment protection work. Target strategic landmarks, factors, limits and border conditions of their attainment and trends of implementation were identified. The specificity of this concept of balanced interaction of society and nature as the basis of sustainable development of the world means implementation of the complex plan of environment protection measures within the frames of ecological-economic policy of the enterprise (on the microlevel) and on the level of national economies (on the global level) aimed at preservation, restoration and increase in environment capital according to the level of adverse impact on nature. Fundamental provisions of the concept should be based on technologies of optimizing modeling of forecast processes and foresight thinking, which identify potentially risky phenomena and threats arising in the space and threatening life on the planet. The author’s fundamental provisions of the concept of balanced interaction of society and nature as a basis of sustainable development of the world are acute not only for Russia but for national economies all over the world. The authors show hope and interest in proliferation of provisions of the given concept under the UN auspices.